(untitled) (Global Journal of Human-Social Science, 2013)
This study was to explore junior high students perception of school climate and school belonging The main purposes of the present study were to test the relationships between school climate and school belonging How s the correlation between the two variables Which one has better effects on the other Three hundred and twenty-eight junior high students in Taiwan were selected to inclusion in the investigation A statistically significant relationship between school climate and school belonging was found From the construction analyses we found that the path coefficients of Model 1 and Model 2 are the same The outcomes meant that school climate had significant effects on school belonging and school belonging also had significant effects on school climate The results of the study can offer the relative schools for evaluating school effects and school improvement